(untitled) (Praxis Educativa, 2026)
This systematic review employs a neuro-sociological framework to analyze how the dialectical interplay among habitus (Bourdieu), executive functions (cognitive flexibility, inhibitory control), and emotional processes shapes teachers’ socioemotional competencies in northern Bogotá. A mixed-methods design synthesizes 78 articles (2013-2023) with critical ethnography. Findings indicate that 78% of educators replicate authoritarian practices ingrained during training, a tendency linked to diminished cognitive flexibility under duress. Structural strain from overcrowded classrooms (>35 students) depletes prefrontal cognitive resources, whereas positive affective states and reflexive practice serve as moderating forces. The study concludes that teacher identity constitutes an embodied construct, necessitating evidence-based interventions that synergistically combine targeted neurocognitive training (e.g., mindfulness) with the critical deconstruction of habitus via decolonial pedagogical approaches.